Effect of activated carbon/graphite on enhancing anaerobic digestion of waste activated sludge - Wu, Fei; Xie, Jiaqian; Xin, Xiaodong; He, Junguo (Frontiers in Microbiology, 2022)
The conductive media was capable to enhance anaerobic digestion and promote direct interspecific electron transfer (DIET). In this study, the effects of activated carbon- and graphite-conductive media on promoting anaerobic digestion efficiency of waste activated sludge were experimentally studied. The results show that the 100 mesh-activated carbon group reactor produced a largest biogas yield of 468.2 mL/g VSS, which was 13.8% higher than the blank test. The graphite group reactor with 400-grain size produced a largest biogas yield of 462.9 mL/g VSS, which was 12.5% higher than the blank test. Moreover, the optimal particle size of such two carbon- conductive mediators were optimized for enhancing degradation efficiency of VSS, TCOD, total protein and total polysaccharide of waste sludge. Activated carbon was capable to promote the hydrolytic acidification stage in anaerobic digestion of waste sludge. When the particle size reduced to the optimal particle size, the promoting effect could be strengthened for producing more hydrolytic acidification products for methanogenesis. However, in the graphite group, the methane production is increased by promoting the consumption of hydrolysis and acidification products and is enhanced with the particle size reduction, thus promoting the methanogenesis process, and improving the anaerobic digestion efficiency. Microbial community analysis showed that both activated carbon and graphite cultivated the genera of Methanosaeta, Methanobacterium, Nitrososphaeraceae, which promoted the improvement of methane production through the acetate debris methanogenesis pathway.